Diurnal variation of cytokinin, auxin and abscisic acid levels in tobacco leaves - Nováková, Marie; Motyka, Václav; Dobrev, Petre I; Malbeck, Jirí; Gaudinová, Alena; Vanková, Radomíra (Journal of experimental botany, 2005)
As many processes are regulated by both light and plant hormones, evaluation of diurnal variations of their levels may contribute to the elucidation of the complex network of light and hormone signal transduction pathways. Diurnal variation of cytokinin, auxin, and abscisic acid levels was tested in tobacco leaves (Nicotiana tabacum L. cv. Wisconsin 38) grown under a 16/8 h photoperiod. The main peak of physiologically active cytokinins (cytokinin bases and ribosides) was found after 9 h of light, i.e. 1 h after the middle of the light period. This peak coincided with the major auxin peak and was closely followed by a minor peak of abscisic acid. Free abscisic acid started to increase at the light/dark transition and reached its maximum 3 h after dark initiation. The content of total cytokinins (mainly N-glucosides, followed by cis-zeatin derivatives and nucleotides) exhibited the main peak after 9 h of light and the minor peak after the transition to darkness. The main, midday peak of active cytokinins was preceded by a period of minimal metabolic conversion of tritiated trans-zeatin (less than 30%). The major cytokinin-degrading enzyme, cytokinin oxidase/dehydrogenase (EC 1.5.99.12), exhibited maximal activity after the dark/light transition and during the diminishing of the midday cytokinin peak. The former peak might be connected with the elimination of the long-distance cytokinin signal. These cytokinin oxidase/dehydrogenase peaks were accompanied by increased activity of beta-glucosidase (EC 3.2.1.21), which might be involved in the hydrolysis of cytokinin O-glucosides and/or in fine-tuning of active cytokinin levels at their midday peak. The achieved data indicate that cytokinin metabolism is tightly regulated by the circadian clock.
Keywords: kyseliny indoloctové; Nicotiana; Cytokinins; glukosidy; Plant Leaves; beta-Glucosidase; cirkadiánní rytmus; Zeatin; regulace genové exprese u rostlin; listy rostlin; Gene Expression Regulation, Plant; Circadian Rhythm; oxidoreduktasy; Abscisic Acid; tabák; Glucosides; zeatin; Indoleacetic Acids; beta-glukosidasa; kyselina abscisová; Oxidoreductases; cytokininy